Impacto de las tic’s post-covid-19 en la gestión del talento humano en el GAD municipal de San Jacinto de Buena Fe, 2023 - Bravo Sánchez, María Fernanda (2025)
The study "Impact of post-COVID-19 ICTs on Human Talent Management in the Municipal GAD of San Jacinto de Buena Fe, 2023" analyzed the transformation of human talent management in a context of rapid digitalization driven by the pandemic. Using a mixed approach, surveys of 99 of 133 officials were combined with interviews with managers, evaluating the impact of ICTs on efficiency, satisfaction, and productivity. The results revealed challenges such as the digital divide and resistance to change, exacerbated by salary disparities and the perception of exclusion among long-time employees, along with opportunities to improve operational efficiency and public service. Limitations in technological infrastructure and training were identified, affecting key processes such as recruitment, selection, training, performance evaluation, and payroll management. The lack of digital platforms, online learning, remote access to biometric systems, and persistence in manual processes generated inefficiencies and frustration. The need for collaborative tools and digitalized citizen service was evident. The original findings include the quantification of the impact improvement in internal communication difficulties in virtual training; and the demonstration of how payroll digitalization reduced times. Strategies such as personalized digital training, online performance management platforms, and collaboration tools were proposed. The research contributes to the National Digital Agenda, offering a model for GADs and emphasizing the need for participatory change management and strategic planning for the effective implementation of ICT.